Transient response of a Mode III interface crack between piezoelectric layer and functionally graded orthotropic layer. (July 2016) - Shin, Jeong Woo; Kim, Tae-Uk
Abstract: In this study, transient response analysis of a Mode III interface crack between a piezoelectric layer and a functionally graded orthotropic material (FGOM) layer is conducted using integral transform techniques. Material properties of the FGOM layer change continuously along the layer thickness and two layers are connected weak-discontinuously. Laplace and Fourier transforms are applied to solve the problem, and the problem is then expressed by a Fredholm integral equation of the second kind. It is found that the followings are beneficial to impede transient fracture of the interface crack between piezoelectric layer and FGOM layer: (a) an increase of shear moduli of the FGOM from the interface to the lower free surface; (b) an increase of the gradient of shear moduli, a decrease of ratio of shear moduli, the electric boundary condition EBC I of the piezoelectric layer in the case of increase of shear moduli of the FGOM from the interface to the lower free surface; (c) an increase of thickness of the layers.